2017
DOI: 10.1055/s-0043-120660
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Thiazol-2-Amines and Their Analogues as Bioactive Molecules: Design, Synthesis, Docking and Biological Evaluation

Abstract: A simple and highly efficient procedure for the synthesis of novel thiazol-2-amines, via Mannich reaction with secondary amines, is described. The newly synthesized derivatives 8(A-E): and 9(A-E): were characterized by H NMR,C NMR, IR, Mass spectroscopy and elemental analysis. All the derivatives were evaluated for their in-vitro anti-microbial activity against a panel of pathogenic strains of bacteria and fungi. The SAR showed that the secondary amines had a significant impact on the in-vitro antimicrobial ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Finally, we revealed selectivity of the thiamine‐dependent regulation of hPdxK, compared with another PLP‐producing enzyme, hPNPO. Interestingly, a recent study has shown that derivatives of thiazol, one of the thiamine constituents, are PdxK inhibitors of potential pharmacological importance (Verma et al, 2018). Physiological relevance of our results is further supported by an evolutionary relationship between thiamine diphosphokinase and PdxK, that is, the vitamin kinases generating the coenzyme forms of the vitamins B 1 and B 6 (Castro‐Fernandez et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we revealed selectivity of the thiamine‐dependent regulation of hPdxK, compared with another PLP‐producing enzyme, hPNPO. Interestingly, a recent study has shown that derivatives of thiazol, one of the thiamine constituents, are PdxK inhibitors of potential pharmacological importance (Verma et al, 2018). Physiological relevance of our results is further supported by an evolutionary relationship between thiamine diphosphokinase and PdxK, that is, the vitamin kinases generating the coenzyme forms of the vitamins B 1 and B 6 (Castro‐Fernandez et al, 2014).…”
Section: Discussionmentioning
confidence: 99%